Writing : a manual for the digital age, brief - Blakesley, David , 1959-; Hoogeveen, Jeffrey Laurence (Wadsworth, 2012)
A handbook for composing in the 21st century. It places students' writing front and center with an innovative page format that keeps students' attention focused on their own writing and on activities, checklists, projects, and visual aids that help them write